Abdul Rahman Model Pembelajaran Student-Centered Learning Dalam Meningkatkan Kompetensi Guru Profesional Abad 21: Model Pembelajaran, Student-Centered Learning, Guru Profesional, Abad 21 - abdul rahman abdul rahman; Baktiar Nasution; Juni Erpida Nasution; Asraini Nasution Nasution (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2025)
This study aims to analyze the strategic role of the Student-Centered Learning (SCL) model in shaping and enhancing the competence of 21st-century professional teachers. Amidst technological disruption and shifting global educational paradigms, the teacher's role is required to transform from a mere information deliverer (Teacher-Centered) into a facilitator and learning designer. This research employs a qualitative approach with a library research method to review scientific literature, policy documents, and best practices related to SCL implementation. The results indicate that the application of SCL functions as an effective catalyst for teacher professional development. Through the process of designing and facilitating active learning, such as Project-Based Learning and differentiated instruction, teachers simultaneously hone pedagogical competence, deepen professional subject mastery, and enhance adaptive social and personality skills. Furthermore, the demands of SCL in the digital era drive the improvement of teachers' digital literacy through the utilization of Learning Management Systems (LMS) and Artificial Intelligence (AI). This study concludes that SCL is not merely a necessity for students but a crucial means to realize a teacher profile that is reflective, innovative, and relevant to contemporary demands.